The insulin-regulated aminopeptidase IRAP is colocalised with GLUT4 in the mouse hippocampus - potential role in modulation of glucose uptake in neurones? - Fernando, Ruani N.; Albiston, Anthony L.; Chai, Siew Y. (The European journal of neuroscience, 2008)
It is proposed that insulin‐regulated aminopeptidase (IRAP) is the site of action of two peptides, angiotensin IV and LVV‐hemorphin 7, which have facilitatory effects on learning and memory. In fat and muscles, IRAP codistributes with the insulin‐responsive glucose transporter GLUT4 in specialised vesicles, where it plays a role in the tethering and/or trafficking of these vesicles. This study investigated whether an analogous system exists in two functionally distinct regions of the brain, the hippocampus and the cerebellum. In the hippocampus, IRAP was found in the pyramidal neurones where it exhibited a high degree of colocalisation with GLUT4. Consistent with the role of GLUT4 in insulin‐responsive tissues, the glucose transporter was thought to be responsible for facilitating glucose uptake into these pyramidal neurones in response to potassium‐induced depolarisation or cAMP activation as the glucose influx was sensitive to indinavir treatment. Angiotensin IV and LVV‐hemorphin 7 enhanced this activity‐dependent glucose uptake in hippocampal slices. In contrast, in the cerebellum, where the distribution of IRAP was dissociated from GLUT4, the effect of the peptides on glucose uptake was absent. We propose that the modulation of glucose uptake by angiotensin IV and LVV‐hemorphin 7 is region‐specific and is critically dependent on a high degree of colocalisation between IRAP and GLUT4. These findings also confirm a role for IRAP and GLUT4 in activity‐dependent glucose uptake in hippocampal neurones.